Impact of Early Surgery and Immunosuppression on Crohn's Disease Disabling Outcomes. Issue 2 (16th January 2017) - Magro, Fernando; Dias, Cláudia C.; Coelho, Rosa; Santos, Paula M.; Fernandes, Samuel; Caetano, Cidalina; Rodrigues, Ângela; Portela, Francisco; Oliveira, Ana; Ministro, Paula; Cancela, Eugénia; Vieira, Ana I.; et al.
Abstract : Background and Aims: The definition of early therapeutic strategies to control Crohn's disease aggressiveness and prevent recurrence is key to improve clinical practice. This study explores the impact of early surgery and immunosuppression onset in the occurrence of disabling outcomes. Methods: This was a multicentric and retrospective study with 754 patients with Crohn's disease, who were stratified according to the need for an early surgery (group S) or not (group I) and further divided according to the time elapsed from the beginning of the follow-up to the start of immunosuppression therapy. Results: The rate of disabling events was similar in both groups (S: 77% versus I: 76%, P = 0.700). The percentage of patients who needed surgery after or during immunosuppression therapy was higher among group S, both for first surgeries after the index event (38% of groups S versus 21% of group I, P < 0.001) and for reoperations (38% of groups S versus 12% of group I, P < 0.001). The time elapsed to reoperation was shorter in group I (HR = 2.340 [1.367–4.005]), stratified for the onset of immunosuppression. Moreover, reoperation was far more common among patients who had a late start of immunosuppression (S36 : 50% versus S0–6 : 27% and S6–36 : 25%, P < 0.001) and (I36 : 16% versus I0–6 : 5% and I6–36 : 7%, P < 0.001). Conclusions: Although neither early surgery nor immunosuppression seem to be able to prevent global disabling disease, an early start of immunosuppression by itself is associated with fewer surgeries and should be considered in daily practice as a preventive strategy.